Space Sciences: Macmillan Science Library - Dasch, Pat (Macmillan Reference USA, 2011)
From the history of space exploration to the future of "space business," this set offers a broad survey of the space sciences. It includes biographies of scientists and the space-related job market. Each illustrated volume includes sidebars, bibliographies, individual and cumulative indexes, and an address listing of the world's space agencies and institutions.